2015
DOI: 10.3920/wmj2015.1900
|View full text |Cite
|
Sign up to set email alerts
|

An integrated targeted and untargeted approach for the analysis of ergot alkaloids in cereals using UHPLC – hybrid quadrupole time-of-flight mass spectrometry

Abstract: Saeger S. (2015). An integrated targeted and untargeted approach for the analysis of ergot alkaloids in cereals using UHPLC -hybrid quadrupole time-of-flight MS. World Mycotoxin Journal 8 (5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…For instance, in our study, speradine A eluted between α-CPA and 2-oxo-CPA, which actually represents the same elution pattern as reported by other researchers [ 33 ]. Similar successful dereplication approaches based on TOF technologies have been reported previously [ 44 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 80%
“…For instance, in our study, speradine A eluted between α-CPA and 2-oxo-CPA, which actually represents the same elution pattern as reported by other researchers [ 33 ]. Similar successful dereplication approaches based on TOF technologies have been reported previously [ 44 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 80%
“… Method 1: Described for the extraction of EAs from rye, based on an extraction with ethyl acetate/MeOH/0.2 mol L ‐1 ammonium bicarbonate pH 8.5 (30 min), phase separation, evaporation, reconstitution in MeOH/MeCN/water, addition of hexane, centrifugation and analysis of the aqueous phase 29 Method 2: Proposed by Guo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning recent occurrence studies about EAs, although the occurrence of main mycotoxins in feed has been extensively studied around the world, 23–26 only a few of these works included EAs 19,26,27 . Moreover, most of the papers including the determination of EAs are focused on cereal grains, 14,28–34 with the inclusion of processed feeds being scarce 19,26,27 . According to the recent available results, the data reported by EFSA in 2017, where a total of 654 feed samples collected in five different countries (Czech Republic, Croatia, Slovenia, the Netherlands and the United Kingdom) between 2011 and 2016, revealed that in more than 50% of these samples, not a single EA was found above the limit of quantification (LOQ).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology applied here can be used in the study of other fungal biosynthetic genes, allowing to identify new compounds that could be of importance in food and feed safety and to assign the genes that are responsible for the production of known fungal secondary metabolites, including mycotoxins. In this regard, the use of molecular networking as a complement de-replication strategy (Yang et al 2013) can be explored, exploiting MS/MS spectra generated in the present study and in previous works Arroyo-Manzanares et al 2015). …”
Section: Discussionmentioning
confidence: 97%